Expression of spleen macrophages in a mouse model of alveolar bone resorption periodontitis: Expression of spleen macrophages - Xu, Yixin; Wang, Yixin; Li, Yongming (Cellular and Molecular Biology, 2023)
It has been shown that macrophages can be endotoxin-tolerant under the stimulation of continuous endotoxin of Porphyromonas gingivalis. Macrophage transforms into M2-type which inhibits inflammation, and its pro-inflammatory cytokine secretion is reduced to avoid the tissue damaged by inflammation. This experiment established the corresponding animal model to explore the relative number, phenotypic proportion, and function of spleen macrophages in mice with chronic periodontitis. Twenty 16-week-old mice were randomly divided into a true ligation group (LFP group) and a pseudo-ligation group (LFC group). The periodontitis in the LFP group was induced by experimental ligation, and the LFC group was treated as a control. After 10 days of ligation, the maxilla was taken, IHC and HE staining were performed to observe the pathological changes of periodontal tissues, and IHC staining was performed to observe the RANKL/OPG ratio. Spleen mononuclear cells were isolated and counted. The ratio of M1 and M2 phenotypes was determined by fluorescence-activated cell sorting (FACS) in the spleen. The relative expression levels of macrophage-associated inflammatory cytokine TNF-a, IL-1β and anti-inflammatory cytokine IL-10 mRNA were detected by real-time PCR. Compared with the control group (LFC:M2/M110.04%), the M2 ratio among spleen mature macrophages in the periodontitis group (LFP: M2/M135.86%) was significantly increased (P<0.01) in the spleen. The proportion of M1 macrophages was not significantly different, and the ratio of M1/M2 was significantly decreased (P<0.05) in the spleen. But the expression level of M1-type macrophage inflammatory factor TNF-a mRNA was inclined. Chronic periodontitis can up-regulate the proportion of M2 macrophages, decrease the ratio of macrophage phenotype M1/M2, and incline the expression of pro-inflammatory factor TNF-a mRNA.